Role Preferences of People with Multiple Sclerosis: Image-Revised, Computerized Self-Administered Version of the Control Preference Scale. - Alessandra Solari; Andrea Giordano; Jurgen Kasper; Jelena Drulovic; An van Nunen; Liina Vahter; Frederique Viala; Erika Pietrolongo; Maura Pugliatti; Carlo Antozzi; Davide Radice; Sascha Köpke; et al. (PLoS ONE, 2013)
The Control Preference Scale (CPS) is the most frequently used measure of patients' preferred roles in treatment decisions. We revised the original CPS and developed a new computerized patient self-administered version (eCPS). We used the eCPS to assess role preferences, and their determinants, in Italian and German people with multiple sclerosis (MS).New cartoons were produced, based on MS health professional and patient input/feedback and previous findings, and pilot tested on 26 Italian and German MS patients. eCPS acceptability and reliability (weighted kappa statistic, wK) in comparison to the original tool, was determined in 92 MS patients who received both CPS versions in random order.The new cartoons were well accepted and easily interpreted by patients, who reported they based their choices mainly on the text and considered the images of secondary importance. eCPS reliability was moderate (wK 0.53, 95% confidence interval [CI] 0.40-0.65) and similar to the test-retest reliability of face-to-face administration assessed in a previous publication (wK 0.65, 95% CI 0.45-0.81). Higher education (odds ratio [OR] 3.74, 95% CI 1.00-14.05) and German nationality (OR 10.30, 95% CI 3.10-34.15) were associated with preference for an active role in the logistic model.The newly devised eCPS was well received and considered easy to use by MS patients. Reliability was in line with that of the original version. Role preference appears affected by cultural characteristics and (borderline statistical significance) education.